The behavior of steel-concrete-steel sandwich beams with different depths effect. (2022) - Alawsi, Manal A.; Mhalhal, Jasim M.; Al-Gasham, Thaar S.; Abid, Sallal R.
Abstract: This research studies the effect of beam depth on the behavior of steel-concrete-steel (SCS) sandwich beams. Four SCS sandwich beams measuring 100 mm wide and 1200 mm length were cast and tested up to failure under three-point flexural loading. The depths in the tested beams ranged from 150 to 300 mm in regular increments of 50 mm. All beams had top and bottom steel skin plates with thickness 4 mm. The shear connector configuration of the Truss using 10 mm diameter steel bars was used to directly connect the two external steel skin plates. The test results confirmed that increasing the depth of the SCS beams from 150 to 300 mm led to an increase in the first cracking load and the ultimate load by 33.5 to 66.5% and 59.2 to 64.2%, respectively. In addition to improving the mechanical properties, when the SCS beams depth was raised to 50%, the service stiffness and secant stiffness both improved by 226.9 and 190.4%, respectively. Moreover, the flexural toughness increased by 101.1% with the SCS sandwich beams depth rising by 25%.